2018
DOI: 10.1016/j.neuropharm.2017.11.049
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin hallucinogen 5-MeO-DMT alters cortico-thalamic activity in freely moving mice: Regionally-selective involvement of 5-HT1A and 5-HT2A receptors

Abstract: 5-MeO-DMT is a natural hallucinogen acting as serotonin 5-HT/5-HT receptor agonist. Its ability to evoke hallucinations could be used to study the neurobiology of psychotic symptoms and to identify new treatment targets. Moreover, recent studies revealed the therapeutic potential of serotonin hallucinogens in treating mood and anxiety disorders. Our previous results in anesthetized animals show that 5-MeO-DMT alters cortical activity via 5-HT and 5-HT receptors. Here, we examined 5-MeO-DMT effects on oscillato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 95 publications
(127 reference statements)
3
35
0
Order By: Relevance
“…The high gamma increase by DOI in conjunction with the high gamma decrease by DPAT supports the notion that 5-HT 1A R and 5-HT 2A R play complementary roles in regulating PFC highgamma oscillations via 5-HT 1A R-and 5-HT 2A R-expressing fast-spiking interneurons, as suggested by our previous work in rats (Puig et al, 2010). 5-HT 2A R agonists such as DOI and lysergic acid diethylamine (LSD) produce hallucinations in human subjects that correlate with increases of PFC metabolism (Nichols, 2004) and, in fact, hallucinogens acting at 5-HT 1A/2A R such as 5MeO-DMT increase PFC gamma oscillations (Riga et al, 2017). Therefore, excessive PFC high-gamma oscillations may underlie the psychotomimetic actions of DOI.…”
Section: Discussionmentioning
confidence: 76%
“…The high gamma increase by DOI in conjunction with the high gamma decrease by DPAT supports the notion that 5-HT 1A R and 5-HT 2A R play complementary roles in regulating PFC highgamma oscillations via 5-HT 1A R-and 5-HT 2A R-expressing fast-spiking interneurons, as suggested by our previous work in rats (Puig et al, 2010). 5-HT 2A R agonists such as DOI and lysergic acid diethylamine (LSD) produce hallucinations in human subjects that correlate with increases of PFC metabolism (Nichols, 2004) and, in fact, hallucinogens acting at 5-HT 1A/2A R such as 5MeO-DMT increase PFC gamma oscillations (Riga et al, 2017). Therefore, excessive PFC high-gamma oscillations may underlie the psychotomimetic actions of DOI.…”
Section: Discussionmentioning
confidence: 76%
“…It has been suggested that this interaction might be the driver of the cortico-striato-thalamo-cortical (CSTC) feedback loop modulation observed in imaging studies (Höflich et al, 2015;Müller et al, 2017;Preller et al, 2018Preller et al, , 2019. Cortical layer 6 contains corticothalamic glutamatergic neurons, which excite thalamocortical relay neurons while disynaptically inhibiting them via exciting GABAergic neurons in the RT (Jones, 2001;Zhang and Jones, 2004;Riga et al, 2018). GABAergic neurons in the RT represent a main inhibitory input to the thalamus and, by means of depolarizing GABA A receptor potential-induced bursts, are involved in the generation of brain electrical oscillations and sleep spindles (Bazhenov et al, 1999;Steriade, 2003).…”
Section: B the Cortico-striato-thalamo-cortical Modelmentioning
confidence: 99%
“…Broadly, at the local network level, 5-HT 2A receptor agonists are observed to modulate glutamate transmission, disrupt typical modes of activity, and facilitate recurrent excitation (Beïque et al, 2007; Wood et al, 2012; Marek, 2018). At the systems level, human neuroimaging studies with psychedelics identify widespread disruptions to thalamocortical (Müller et al, 2017; Preller et al, 2018; Riga et al, 2018) and cortico-cortical connectivity, leading to alterations of classical functional connectivity networks and changes in neuronal dynamic properties (Kometer et al, 2013; Muthukumaraswamy et al, 2013; Carhart-Harris et al, 2014; Carhart-Harris, 2018; Mason et al, 2020; Preller et al, 2020). However, which observed neuronal effects are specific to, and characteristic of, the psychedelic state, remains to be further dissected (Roseman et al, 2014; Müller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%